A study on developing 3-dimensional architecture array of solar park above railways. (2021) - Muniraja Chandra, P.; Shabir, Mohd F.; Manikandan, R.; Prabakaran, L.; Mujeeb Khan, H.; Narayana Murthy, B.; Selvi, S.
Abstract: Energy generation through solar has become more tedious due to huge investment required over its equipment and land. Though the equipment cost factor can be managed by latest technologies, availability of land has become a major setback for the development of solar industries. To eliminate the land requirement for power generation using solar, a concept has been proposed to use the available railway lines for dual purpose. A deck can be formed above 10 m from the ground level to establish a solar park of capacity of 50, 000 MW using 300 Wp monocrystalline PV module at a cost of 5 trillion rupees, which includes module, civil works, installation, commissioning, operation and maintenance cost for a period of 25 years with Return of Investment in 10 years. If the concept is implemented throughout India, it not only increases the power generation capacity through renewable energy but also has other various benefits including longer life of rail tracks & coaches, employment opportunities and reduce CO2 emission in environments.